(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2026)
Background: Emergency conditions in the Emergency Department (ED) often cause anxiety among patients’ families due to uncertainty and limited information. Objective: This study aimed to analyze the effect of Patient Family Education on the anxiety levels of patients’ families in the ED. Method: A traditional literature review was conducted on national and international articles published between 2021 and 2025, obtained from Google Scholar and PubMed using the keywords “Family Education,” “Family Anxiety,” and “Emergency Department.” Articles meeting the inclusion criteria were analyzed using content analysis, resulting in three reviewed articles. Discussion: The findings indicate that Patient Family Education significantly reduces family anxiety levels in the ED. In addition, age, gender, educational level, patient condition, and the role of nurses also influence family anxiety.Conclusion: Family education is an effective nursing intervention for reducing anxiety among patients’ families in the Emergency Department.